Kober fractional q-integral operator of the basic analogue of the H-function - Saxena, R.K.; Yadav, R.K.; Purohit, S.D.; Kalla, S.L. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper deals with the derivation of the Kober fractional q-integral operator of the basic analogue of the H-function defined by Saxena, Modi and Kalla [Rev. Téc. Ing., Univ. Zulia. 6(1983), 139-143]. Several interesting results .involving Gq(.);Eq(.); the basic elementary functions and the basic Bessel functions such as Jv(x; q); Yv(x; q); Kv(x; q); Hv(x; q), are deduced as the special cases of the main results.